Public Costs of Florida Red Tides, 2007 - Kimberly L. Morgan; Sherry L. Larkin; Charles M. Adams (EDIS)
FE711, a 4-page executive summary by Kimberly L. Morgan, Sherry L. Larkin, and Charles M. Adams, summarizes Public Costs of Florida Red Tides: A Survey of Coastal Managers, a study which attempted to quantify public expenditures and procedures resulting from red tide-related management and mitigation issues. Includes references. Published by the UF Department of Food and Resource Economics, June 2008.